2000
DOI: 10.1093/cercor/10.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissociation between Medial and Lateral Prefrontal Cortical Spatiotemporal Activation in Negative and Positive Emotions: A Combined fMRI/MEG Study

Abstract: The orbitofrontal cortex has been cytoarchitectonically and connectionally subdivided into a medial and a lateral part which are assumed to subserve distinct functions in emotional processing. However the exact spatiotemporal mechanisms of negative and positive emotional processing in medial and lateral orbitofrontal cortex remain unclear. We therefore investigated spatiotemporal orbitofrontal and prefrontal cortical activation patterns during emotional stimulation in a combined fMRI/MEG study. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
150
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(172 citation statements)
references
References 61 publications
17
150
1
4
Order By: Relevance
“…Single-unit recording in human orbital frontal cortex showed increased firing rates to aversive stimuli including facial expressions of fear (32). Similar increases in orbital frontal activity were measured with functional imaging to angry expressions (33), to aversive stimuli (34), and to the actual induction of anger (35,36). Disruption of the medial prefrontal cortex by transcranial magnetic stimulation caused a delay in the recognition of angry faces but not happy faces (37).…”
Section: Discussionsupporting
confidence: 56%
“…Single-unit recording in human orbital frontal cortex showed increased firing rates to aversive stimuli including facial expressions of fear (32). Similar increases in orbital frontal activity were measured with functional imaging to angry expressions (33), to aversive stimuli (34), and to the actual induction of anger (35,36). Disruption of the medial prefrontal cortex by transcranial magnetic stimulation caused a delay in the recognition of angry faces but not happy faces (37).…”
Section: Discussionsupporting
confidence: 56%
“…This finding has supported a model whereby the medial orbitofrontal cortex codes for pleasantness and the lateral orbitofrontal cortex codes for unpleasantness (16). However, running counter to this model, some studies have found increased medial OFC activity to negative stimuli or increased lateral OFC activity to positive stimuli (17)(18)(19). These conflicting results indicate that, for valance encoding in the OFC, the distinction between medial and lateral might be not as simple as the encoding of positive as opposed to negative stimuli and might depend on stimulus modality and complex aspects of stimulus processing.…”
Section: Discussionmentioning
confidence: 93%
“…However, some studies have found medial OFC activity to negative stimuli or lateral OFC activity to positive stimuli (17)(18)(19). Key issues in understanding these discrepancies include sensory modalities of presented stimuli, stimulus characteristics that may confound valence differences, and individual subject differences, such as menstrual cycle phase in female subjects.…”
mentioning
confidence: 99%
“…These regions share extensive reciprocal connections with the amygdala, anterior temporal and anterior cingulate cortex (Ongur and Price, 2000). Functional neuroimaging studies in healthy subjects have demonstrated a role for the medial and lateral sectors of the IFC in mood regulation (Baker et al, 1997;Northoff et al, 2000) and in emotional memory (Cabeza and Nyberg, 2000). It has been speculated that the IFC is involved in the highest level of behavior regulation, including emotion regulation, through pathways between the IFC and autonomic systems that govern visceral responses associated with affective stimuli (Cabeza and Nyberg, 2000).…”
Section: Discussionmentioning
confidence: 99%